ASSESSMENT OF HEAVY METAL CONTAMINATION AND SEASONAL VARIATION IN RIVER GWAGWALADA, NIGERIA - Nda Amlabu, Elias; Mohammed Evuti, Abdullahi; Isah Abdulkarim, Bala; Abdurrahman, Abdulwasiu; Olanrewaju, Kamiludeen; Yakubu, Stephen; Zakari, Abdullahi (FUDMA Journal of Sciences, 2026)
Heavy metals are among the most persistent pollutants in aquatic environments due to their toxicity, persistence, and potential for accumulation. Rivers receiving discharges from industrial, domestic, and agricultural activities are particularly vulnerable to contamination. This study investigated the concentrations and seasonal variations of seven heavy metals (Cd, Cr, Co, Fe, Mn, Ni, and Zn) in River Gwagwalada, Abuja, Nigeria. Water samples were collected from twelve sampling stations during the rainy and dry seasons and analyzed using Atomic Absorption Spectrophotometry (AAS). The mean concentrations (mg/L) were Cd (0.06), Co (0.114), Cr (0.19), Fe (1.71), Mn (0.29), Ni (1.14), and Zn (0.01). Comparison with WHO (2011) drinking-water guidelines revealed that Mn and Zn were within permissible limits, whereas Cd, Co, Cr, Fe, and Ni exceeded the recommended values. Analysis of variance (ANOVA) showed significant seasonal variations in the concentrations of Co, Cr, Fe, Mn, and Ni, while Cd and Zn exhibited no significant differences between the rainy and dry seasons. The observed spatial and seasonal variations suggest that anthropogenic activities, including agricultural practices, domestic waste disposal, sewage discharge, and urban runoff, contribute to heavy metal contamination in the river. The findings highlight the need for regular water-quality monitoring and effective pollution-control measures to support the sustainable management of River Gwagwalada.